2005
DOI: 10.3354/dao067217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triclosan on growth viability and fatty acid synthesis of the oyster protozoan parasitePerkinsus marinus

Abstract: Perkinsus marinus, a protozoan parasite of the Eastern oyster Crassostrea virginica, has severely impacted oyster populations from the Mid-Atlantic region to the Gulf of Mexico coast of North America for more than 30 yr. Although a chemotherapeutic treatment to reduce or eliminate P. marinus from infected oysters would be useful for research and hatchery operations, an effective and practical drug treatment does not currently exist. In this study, the antimicrobial drug triclosan 5-chloro-2-(2, 4 dichloropheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Indeed, it has been shown that Perkinsus proliferation is inhibited by Triclosan and cerulenin, which has been interpreted as evidence for the presence of a plastidic FAS II pathway [24,25]. However, when considering the effect of Triclosan as indicative of the relevance of the apicoplast FASII biosynthesis, results should be interpreted with caution, since in Plasmodium , the antimalarial activity of Triclosan is not targeted to FabI [90].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that Perkinsus proliferation is inhibited by Triclosan and cerulenin, which has been interpreted as evidence for the presence of a plastidic FAS II pathway [24,25]. However, when considering the effect of Triclosan as indicative of the relevance of the apicoplast FASII biosynthesis, results should be interpreted with caution, since in Plasmodium , the antimalarial activity of Triclosan is not targeted to FabI [90].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of P. marinus, it may be possible to use K3 anilide herbicides to control their infection of oysters, as the toxicity of compounds such as flufenacet, although severe toward terrestrial and aquatic plants, shows much reduced (several orders of magnitude) toxicity to non-photosynthetic organisms including the eastern oyster (see www.epa.gov/opprd001/ factsheets/flufenacet.pdf). An analogous approach to controlling P. marinus has recently been proposed using the type II fatty acid synthase inhibitor triclosan (31). Alternatively, the knowledge that flufenacet disrupts the P. marinus FAE elongase, and by implication the synthesis of ARA, may serve as the basis for chemical design and synthesis of more specific inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Parasitic protozoa must either acquire lipids from their host or synthesize lipids de novo to produce the new cell membrane during cell replication. Inhibiting the ability to synthesize new membrane prevents the parasite from increasing in surface area, thereby halting cell proliferation and disease progression [134]. Triclosan has demonstrated an inhibitory effect on the growth of Plasmodium falciparum, Toxoplasma gondii, Theileria parva, Trypanosoma brucei and Perkinsus marinus in in vitro studies, and in in vivo studies with P. berghei in a mouse model [134-138].…”
Section: Anti-babesia Drugsmentioning
confidence: 99%